Performance analysis of the CAC scheme CARETON under mixed cell environment in overlay networks. (8th June 2011) - Mukhopadhyay, Asish K.; Khara, Sibaram; Saha, Sajal; Saha, Debashis
The paper proposes a call admission control (CAC) scheme to offer best services to the users in the next generation heterogeneous networks. It optimises the available resources without compromising the interest of the service providers. It has combined the three commonly used CAC schemes – guard channel, buffer-based and priority-based schemes. It considers wireless overlay model for analysing the heterogeneity with detailed analysis of the WLAN-cellular mixed cell environment. The scheme considers differentiated services for the real time and non-real time calls to provide appropriate quality of service (QoS). The proposed scheme has been evaluated through simulation. The results show that the scheme outperforms some significant CAC schemes and shows even better performance under cellular-WLAN mixed environment due to the dual subscription of the users with dual mobile terminal.